Papers relating to the Papua New Guinea House of Assembly research project - Gadbois, George H. (George Harold), 1936-; Papua New Guinea. House of Assembly; Australian National University. Pacific Manuscripts Bureau (1964)
The papers of George H. Gadbois relating to the Papua New Guinea House of Assembly research project comprise interview recordings, transcripts and research papers. They include transcripts of interviews with backbenchers in the Papua New Guinea House of Assembly, 1974; a code book interview schedule and research committee paper; lists of the members of the House of Assembly, 1964-1976; and, research files and publications.
Microfilm.
Microfilmed from originals held at: Pacific Research Archives, ANU Archives Program, Australian National University, Canberra.
George H. Gadbois, Jr., was born in Boston, Mass., in 1936 and is a retired University of Kentucky political science professor. For his two papers, Elections in Papua New Guinea: a search for a framework of analysis (1977), and The representative roles and accountability of legislators in Papua New Guinea (1978), Gadbois drew on the research he conducted in Papua New Guinea during the second half of 1974. The subject of his research involved 73 backbenchers of the Papua New Guinea House of Assembly. They were interviewed using questions contained in the Interview Schedule for Legislators. The interviews were conducted in English, Tok Pisin and Motu; written (typescript) versions are all in English. Most of the interviews were conducted by University of Papua New Guinea students with the interviewers frequently identified in the written version. A memorandum from Gadbois to an (unspecified) research committee provides a rationale for the form of the study.
Keywords: Papua New Guinea. -- House of Assembly -- Interviews; Politicians -- Papua New Guinea -- Interviews; Papuans -- Interviews; Papua New Guinea -- Politics and government -- To 1975.